Natural killer cell education does not affect the magnitude of granzyme B delivery to target cells by antibody-dependent cellular cytotoxicity. (31st July 2015) - Isitman, Gamze; Lisovsky, Irene; Tremblay-McLean, Alexandra; Parsons, Matthew S.; Shoukry, Naglaa H.; Wainberg, Mark A.; Bruneau, Julie; Bernard, Nicole F.
<x xml:space="preserve">Abstract</x> Objective: Interest in the role of antibody-dependent cellular cytotoxicity (ADCC) in protection from HIV infection has grown since analyses of the RV144 HIV vaccine trial results found ADCC correlated with protection. Natural killer (NK) cells are among the effector cells that mediate ADCC. The level of antibody-induced NK cell activation depends on NK cell education through inhibitory NK cell receptor human leukocyte antigen (HLA) ligand interactions. Here, we investigated the impact of NK cell education on the delivery of Granzyme B (GzB) to target cells. Design: Lymphocytes from 50 HIV-uninfected [30 Bw4+ (Bw4) and 20 Bw4- (Bw6)] KIR3DL1 homozygote persons were used as effectors and cocultured with gp120-coated target cells in the presence of a single source of anti-HIV gp120 antibody to ascertain whether NK cell education status influenced the level of GzB delivered to target cells. Methods: The GTL assay assessed the frequency of GzB-positive (%GzB+) CEM.NKr.CCR5 target cells generated by effectors from each individual. The frequency of CD107a+, interferon (IFN)-γ+ and CCL4+ NK cells was assessed as a measure of antibody-induced NK cell activation. Results: KIR3DL1+ NK cells from the Bw4 group were more functional than KIR3DL1- NK cells. Despite this, the %GzB+ target cells generated in the GTL assay did not differ according to the KIR3DL1-HLA-B genotype of the effector cells. The %GzB+ cells positively correlated with the frequency of CD16+KIR3DL1− NK cells in the effector population. Conclusion: ADCC potency does not depend on NK cell education.